ANALISIS KEPENTINGAN EKONOMI TIONGKOK DALAM KERJASAMA EKONOMI DIGITAL ASEAN MELALUI DIGITAL SILK ROAD - Orlandawati, Viviana Putri; Wiranata, I Made Anom; Parameswari, Anak Agung Ayu Intan; Orlandawati, Viviana Putri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
This research aims to analyze China's economic interests in digital economic cooperation with ASEAN countries through the Digital Silk Road initiative. In the era of economic globalization and advances in information technology, this collaboration has become the focus of attention in the regional and global economic landscape. This research uses a qualitative approach by collecting data from primary and secondary sources, including the study of official government documents. This research tries to answer questions related to how China views this cooperation from an economic perspective and what economic interests China hopes to gain from this cooperation. The findings of the economic interests of ASEAN digital economic cooperation through the Digital Silk Road are the development of Chinese national companies, internationalization of the reminbi, expanding the expansion of China's technology market globally, and accelerating digital economic cooperation between China and ASEAN. It is hoped that this research will provide insight into the dynamics behind digital economic cooperation between China and ASEAN, as well as its implications for both parties in the context of regional and global digital economic development. Keywords: ASEAN, Digital Silk Road, Economic Interests, China